2020
DOI: 10.1177/1363459320954237
|View full text |Cite
|
Sign up to set email alerts
|

Mass media and communication interventions to increase HIV testing among gay and other men who have sex with men: Social marketing and visual design component analysis

Abstract: Mass media and communication interventions can play a role in increasing HIV testing among gay, bisexual and other men who have sex with men (GBMSM). Despite the key role of social marketing principles and visual design within intervention development of this type, evidence is limited regarding interventions’ social marketing mix or visual design. As part of a systematic review, intervention content was assessed using social marketing theory and social semiotics. Data were extracted on the nature of the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…We show that exposure to any form of media such as TV, radio and print increases the likelihood of HIV testing. This positive correlation is congruous with other findings in different countries [23,24]. Similarly, studies in Bangladesh and North India also showed a significant association between media exposure and HIV awareness [25,26] With regard to behavioural risk factors among women in PNG, several studies support the involvement of behavioural risks factor in HIV testing among women of reproductive age [9] and previous knowledge of their HIV status [27].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We show that exposure to any form of media such as TV, radio and print increases the likelihood of HIV testing. This positive correlation is congruous with other findings in different countries [23,24]. Similarly, studies in Bangladesh and North India also showed a significant association between media exposure and HIV awareness [25,26] With regard to behavioural risk factors among women in PNG, several studies support the involvement of behavioural risks factor in HIV testing among women of reproductive age [9] and previous knowledge of their HIV status [27].…”
Section: Discussionsupporting
confidence: 61%
“…A total of 15,198 women of reproductive age were included in this study. The median (IQR) age at the time of the study was 28 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) years, that at first sex 18 (16)(17)(18)(19)(20)(21) years and that at first cohabitation 19 (17)(18)(19)(20)(21)(22) years. The majority of the women were Christian (99.0%), and 95.3% had never used condoms.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the non-Western interventions we identified through our search strategy are striking for how they move beyond the highly individualized nature of the sexual subject that forms the basis of most other interventions whilst at the same time eschewing a porn aesthetic. Whilst the cultural context may be a factor in the success (or not) of different (individualistic vs. collectivist) strategies, it may also be the case that these decisions are being based on the ideologies of the researchers and/or those commissioning the work, alongside key contextual factors such as where such images are being deployed (see Riddell et al, under review , for more on this), rather than empirical evidence concerning the effectiveness of particular affects within particular cultural contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The study is also limited through an analysis that is distanced from the original intended context of the intervention, with images subject to critical analysis outside of their original viewing context (see Riddell et al, under review , for more on this). Also, ideally, it would be possible to map this analysis of affect and ideology to effectiveness but that was not possible in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation